ВЗАЄМОЗВ’ЯЗОК ФОРМУВАННЯ МОВНОЇ ОСОБИСТОСТІ СТУДЕНТА ВНЗ НЕФІЛОЛОГІЧНОГО ПРОФІЛЮ З РОЗВИТКОМ ПРОФЕСІЙНОГО МОВЛЕННЯ - Дроздова, Ірина (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті досліджується мовна особистість студента нефілологічного профілю, що формується у процесі навчання української мови у вищій школі. З’ясовано, що на формування мовної особистості впливають як незалежні від особи мовця об’єктивні, так і суб’єктивні чинники. Методика викладання української мови у вищій школі формується з методики викладання української мови на філологічних факультетах і методики викладання української мови для студентів нефілологічного профілю. Зауважено, що необхідний рівень професійної українськомовної комунікативної компетенції студента ВНЗ нефілологічного профілю передбачає наявність у нього комунікативних та професійно-комунікативних умінь. В статье исследуется языковая личность студента нефилологического профиля, которая формируется в процессе обучения украинского языка в высшей школе. Выяснено, что на формирование языковой личности влияют как независимые от лица говорящего объективные, так и субъективные факторы. Методика преподавания украинского языка в высшей школе формируется по методике преподавания украинского языка на филологических факультетах и методики преподавания украинского языка для студентов нефилологического профиля. Замечено, что необходимый уровень профессиональной украиноязычной коммуни-кативной компетенции студента вуза нефилологического профиля предполагает наличие у него коммуникативных и профессионально-коммуникативных умений. This article examines the linguistic identity of students of non-philological profile, which is formed in the process of learning the Ukrainian language in higher school. It was found that the formation of linguistic identity affect both independent speaking on behalf of objective and subjective factors. Methods of teaching Ukrainian language in the higher school is formed by a technique of teaching of the Ukrainian language in the faculties of Philology and methods of teaching Ukrainian language for students of non-philological profile. In the learning process in a higher educational institution, the student reoriented to adequate their chosen profession the choice of means of communication, and formed a professional language personality and language professional communicative competence. This concept is more narrow on the notion of communicative competence, since the criteria of professional activity determine whether the sender of the speech of a number of communicative skills specific and is required only for this activity. It is noticed that the necessary level of Ukrainian-language professional communicative competence of university students of non-philological profile suggests the presence of communicative and professional communication skills.